2022
DOI: 10.3390/cells11203298
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide Nanoparticles Combined with Static Magnetic Fields in Bone Remodeling

Abstract: Iron oxide nanoparticles (IONPs) are extensively used in bone-related studies as biomaterials due to their unique magnetic properties and good biocompatibility. Through endocytosis, IONPs enter the cell where they promote osteogenic differentiation and inhibit osteoclastogenesis. Static magnetic fields (SMFs) were also found to enhance osteoblast differentiation and hinder osteoclastic differentiation. Once IONPs are exposed to an SMF, they become rapidly magnetized. IONPs and SMFs work together to synergistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 112 publications
1
12
0
Order By: Relevance
“…Similar trends were noted for BSP and OC, which are both known markers of late-stage bone differentiation. These results indicate that the magnetic microenvironment provided by Fe 3 O 4 nanoparticles in Fe 3 O 4 scaffolds promoted cell proliferation and differentiation in a time- and dose-dependent manner [ 21 ]. Moreover, the stem cells cultured on the scaffold experienced increased osteogenic differentiation, ALP secretion, and calcium deposition compared to those seeded on scaffolds without Fe 3 O 4 , indicating that the osteogenic differentiation of stem cells was significantly regulated by the incorporation of Fe 3 O 4 into ceramics [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar trends were noted for BSP and OC, which are both known markers of late-stage bone differentiation. These results indicate that the magnetic microenvironment provided by Fe 3 O 4 nanoparticles in Fe 3 O 4 scaffolds promoted cell proliferation and differentiation in a time- and dose-dependent manner [ 21 ]. Moreover, the stem cells cultured on the scaffold experienced increased osteogenic differentiation, ALP secretion, and calcium deposition compared to those seeded on scaffolds without Fe 3 O 4 , indicating that the osteogenic differentiation of stem cells was significantly regulated by the incorporation of Fe 3 O 4 into ceramics [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the magnetic microenvironment provided by Fe 3 O 4 nanoparticles in Fe 3 O 4 scaffolds promoted cell proliferation and differentiation in a time- and dose-dependent manner [ 21 ]. Moreover, the stem cells cultured on the scaffold experienced increased osteogenic differentiation, ALP secretion, and calcium deposition compared to those seeded on scaffolds without Fe 3 O 4 , indicating that the osteogenic differentiation of stem cells was significantly regulated by the incorporation of Fe 3 O 4 into ceramics [ 21 ]. Xia et al demonstrated that Fe 3 O 4 -containing bioceramic scaffolds stimulated the osteogenic differentiation of stem cells and significantly upregulated the gene expression of WNT1, RUNX2, ALP, COL1, and OCN [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SPION biological scaffolds are generally implanted into the target bone defects without adding an SMF or under the action of one to stimulate bone tissue repair, regeneration, healing, and so on. When exposed to SPION magnetic biological scaffolds, osteoblasts, BMSCs, and DPSCs showed active migration, proliferation, and differentiation, while osteoclasts showed abnormal behavior, which may be attributed to the effect of the micromagnetic field, the magnetic mechanical stimulation, and the increase in the intracellular SPION level in the presence of an SMF [ 91 ]. At the same time, the expression levels of some genes and cellular molecules related to osteogenesis are significantly increased, which further promotes the repair of bone and cartilage defects.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic biomaterials also have great application potential in the field of bone tissue engineering. At present, the most commonly used magnetic particles in magnetic biomaterials are iron powder, iron trioxide, iron tetroxide, and so on [ 20 , 91 ]. The commonly used synthesis methods are freeze-drying, electrospinning, three-dimensional (3D) printing, chemical synthesis, and other methods ( Figure 1 ).…”
Section: Biological Scaffolds Assembled With Magnetic Iron Oxide Comp...mentioning
confidence: 99%